2023
DOI: 10.1007/s10008-023-05472-3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of magnesium alloy AZ31 in chloride-containing solutions by aqueous permanganate

Abstract: In this work, corrosion of the AZ31 magnesium alloy was examined in 0.05 M NaCl solutions containing 0.01–0.150 mol/dm3 of potassium permanganate as a corrosion inhibitor. A set of electrochemical impedance spectroscopy, linear sweep voltammetry, and hydrogen evolution measurements revealed high inhibitor effectiveness at relatively high (0.150 mol/dm3) KMnO4 concentrations. Based on data of energy-dispersive X-ray analysis, scanning electron microscopy, and Raman spectroscopy, a mechanism of the corrosion inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This results in an increased current density over unprotected areas and, consequently, an increased corrosion rate. The same behavior was previously observed for the WE43 and AZ31 alloys in the case of the molybdate and permanganate inhibitors [31,38,39]. At higher added concentrations, Na2MoO4 caused a pronounced decrease in icorr.…”
Section: Evolution Of Ph and Ocp At Initial Stages Of Corrosion In Ch...supporting
confidence: 83%
See 3 more Smart Citations
“…This results in an increased current density over unprotected areas and, consequently, an increased corrosion rate. The same behavior was previously observed for the WE43 and AZ31 alloys in the case of the molybdate and permanganate inhibitors [31,38,39]. At higher added concentrations, Na2MoO4 caused a pronounced decrease in icorr.…”
Section: Evolution Of Ph and Ocp At Initial Stages Of Corrosion In Ch...supporting
confidence: 83%
“…The latter usually act as precipitation-type inhibitors and their effectiveness is strongly related to the microstructure of a Mg alloy, since the inhibition is usually based on retarding the cathodic activity of IMPs. In our previous works [31,38,39], we have shown that inorganic oxidizing anions, such as permanganates and molybdates, are effective inhibitors for the corrosion protection of AZ31 and WE43 alloys. In the case of the AZ31 alloy, the inhibition mechanism is based on the formation of a surface oxide layer suppressing the cathodic activity of IMPs and the anodic activity of the Mg matrix.…”
Section: Continuous Technological Development and Search For New Ener...mentioning
confidence: 98%
See 2 more Smart Citations
“…Nyquist plots of the uncoated and anodized ZK60A alloy obtained in 3.5 wt.% NaCl solution at room temperature are shown in Figure 10a. The diameter of the semicircle is associated with the charge transfer resistance of the electrode surface [55,56]. The plot of the uncoated ZK60A alloy can be barely seen in Figure 10a, as it exhibits a capacitive loop whose diameter is much smaller than those of the anodized samples, thus indicating that the anodizing treatment greatly enhanced the corrosion resistance of the alloy.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%